Implementation of Multicultural and Moderate Islamic Education at the Elementary Schools in Shaping the Nationalism - Subandi, Subandi; Fauzan, Ahmad; Afriyadi, Muhammad Muchsin; Ramli, Mispani (Universitas Islam Negeri Raden Intan Lampung, 2019)
Islamic multicultural education in formal education can be implemented since elementary school. The purpose of this article is to describe the application of multicultural education with moderate Islamic values through the learning process in elementary schools to shape the character of nationalism in Indonesia. The qualitative method was used in this study to see the phenomena that occur in the field. The data analysis used was the source and technique triangulation method. There were 8 respondents from three elementary schools, namely Sekolah Dasar Negeri 7 Kota Metro, Sekolah Dasar Negeri 4 Kota Metro, and Madrasah Ibtidaiyah Negeri 1 Kota Metro. The research instruments used were interviews, observations, and documentation, which were then analyzed through inductive thinking. The development of multicultural education and moderate Islamic values in shaping the character of nationalism was done through the integration of moderate Islam by instilling tawassuth, tassamuh, tawazun, and amar ma'ruf nahimunkar attitudes by introducing the surrounding environment as a cultural plurality (contextual approach) and instilling an attitude of tolerance and able to coexist with other people. These three steps were developed by the teachers in structured lesson planning by formulating goals, setting essential material, carrying out the learning process, and carrying out attitude assessments.